Application of Sentinel-1 data to quantify Arctic Coastal Retreat - Holsten, Henry (author) (2021)
In the arctic region many coastal areas exhibit rapid erosion, with coastal retreat or erosion rates of 10 meters per year (m/yr.) or higher in places. This poses a threat primarily to all manner of infrastructure built directly on and near the coastline. With climate change the coastal erosion is expected to increase. This effect is expected to be especially severe in the continuous permafrost region, as the coastal erosion is linked with the increase in thermoerosion of the permafrost. A remote sensing method with high coverage and sufficient temporal observation frequency at lower cost than from aerial photography would be practical to mitigate the problem. This would enable assessing and predicting (potential) damage to existing infrastructure and planning of its future locations. A thresholding method based on TerraSAR-X x-band synthetic aperture radar observations is applied to lower resolution Sentinel-1 c-band synthetic aperture radar observations monitor the coastal erosion rates. This study aims to determine the feasibility of using this method with Sentinel- 1 data. For this purpose, the method is applied to Senteinel-1 Backscatter scenes and the Coherence between scenes within each year from 2016 to 2020 at three sample sites on Herschel Island (Beaufort Sea, northern Canada). The method was successfully applied to the Sentinel-1 Backscatter data, yielding reliable and accurate results for one of the sample sites, with the highest estimated erosion rate of the three sites. The same technique was applied to the Coherence data. The obtained results were less reliable compared to the results from the Backscatter data, showing too high variance. The results indicate that the application is generally limited to the summer season and to coastlines oriented towards or parallel to the looking direction of the SAR sensor. The results are compared to previous studies of coastal erosion rates on Hershel Island or the nearby northern Yukon coastline region. Applied Geophysics | IDEA League